PELATIHAN PENYUSUNAN LAPORAN LABA RUGI DAN TOKO ONLINE “JW.SPEEDSHOP” - Agnes Andrea; Hendro Lukman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
ABSTRACT The rapid development of technology is driving economic growth, leading to the emerge of many Micro, Small, and Medium Enterprises (MSMEs) that operate through digital platforms (e-commerce). In their operational activities, digital MSMEs often face constrains in implementing financial literacy, particularly in applying accurate expense recording, calculating profit and loss, and separating personal funds from business funds. A similar problem was experienced by the author’s partner, JW.SPEEDSHOP, in the implementation of this Community Service Programme. As a solution to the partner’s problem, the author provided training on the structure of a profit and loss statement, the definitions of expenses, revenue, and profit, as well as methods for separating personal and business funds. The training was carried out in three stages: the delivery of material, provision of a profit and loss statement framework reference, discussion between author and partner on ways of recording revenue and expenses, and the creation of the partner’s profit and loss report for one month period during September 2025. Based on the results of the profit and loss Statement prepared by the partner, along with the partner’s response regarding their level of understanding, it can be concluded that the partner was able to understand the training material delivered by the author. Perkembangan pesat teknologi mendorong pertumbuhan ekonomi yang memunculkan banyak Usaha Mikro, Kecil, dan Menengah (UMKM) yang beroperasi melalui platform digital (e-commerce). Dalam kegiatan operasionalnya, UMKM digital sering mengalami kendala dalam menerapkan literasi finansial, terutama dalam menerapkan pencatatan beban, perhitungan laba rugi, serta pemisahan dana pribadi dengan dana usaha. Masalah yang serupa dialami oleh mitra Tim PKM, yaitu JW.SPEEDSHOP dalam pelaksanaan PKM ini. Sebagai solusi dari permasalahan mitra, Tim PKM memberikan pelatihan mengenai susunan laporan laba rugi, definisi beban, pendapatan, dan laba, serta metode pemisahan dana pribadi dengan dana usaha. Pelatihan dilakukan dalam tiga tahapan, yaitu: pemberian materi, pemberian referensi kerangka laporan laba rugi, diskusi mengenai pencatatan pendapatan dan beban yang terjadi, serta pembuatan laporan laba rugi mitra untuk periode 1 bulan selama bulan September 2025. Melalui hasil pembuatan laporan laba rugi oleh mitra yang disertai dengan hasil respons mitra terhadap tingkat pemahaman mitra, dapat disimpulkan bahwa mitra mampu memahami materi pelatihan yang telah Tim PKM sampaikan.